Ludic exercises to improve coordination in football players in the training stage - Reimundo Gualotuña, Brenda Paola; Aguilar Morocho, Elva Katherine (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
The objective of this research was to develop a ludic exercise plan that helps to improve coordination in football in formative stages, strengthen the teaching methodology at these ages and understand that the ludic part is essential in the development of all kinds of learning; in this case in football and its different techniques. For this study, a sample of 9 children was taken from the football sports school located in the city of Quito, Carcelén sector; eight boys and one girl, to whom the 3JS coordination test was applied, with which we evaluated their level of coordination through a pre-test. From this data we focus on the development of recreational exercises that allow us to improve their motor experience and, in this way, the correct development of techniques in football. Finally, a post test was carried out, with which we analyzed whether there are significant differences and the comparison between the pre and post test, which indicates that the recreational exercises were effective in improving coordination in the children.